Cardiac Amyloidosis Masquerading as Hypertrophic Obstructive Cardiomyopathy: Co-existence or Coincidence? - Madhu Shukla; Jagdish Chander Mohan (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging)
A 59-year-old male presented with syncope and nonsustained ventricular tachycardia and was diagnosed to have hypertrophic obstructive cardiomyopathy. He underwent dual-chamber implantable converter defibrillator (ICD) insertion. Following ICD insertion, in view of some red flags, routine cardiac magnetic resonance imaging was performed, which showed biventricular hypertrophy, diffuse subendocardial gadolinium enhancement of both the ventricles, prolonged T1 and T2, and left ventricular extracellular volume fraction of 50%. A pyrophosphate scan of the heart was strongly positive both at 1 and 3 h intervals. M-band was observed on plasma protein electrophoresis. Serum and urinary immunofixation studies suggested lambda light-chain gammopathy. Multiparametric flow cytometry of the bone marrow aspirate revealed 20% plasma cells immunophenotyped to produce only light-chain immunoglobulins. The patient is on specific chemotherapy for the past 7 months and is asymptomatic.